Él: de Mercedes Pinto a Luis Buñuel - Cummings, Gerardo (2004)
Mercedes Pinto's Él is one of most often overlooked Hispanic novel s by critics and scholars. This text served as the basis for Luis Buñuel's 1953 film of the same name and it offers many topics of possible discussion: from spousal abuse to the role of patriarchy in the life of a Hispanic woman, it is ripe for a contemporary critical analysis. The story that both texts share can be synthesized as the trials and tribulations of a woman and her paranoid-schizophrenic husband. Pinto's work lacks a definite time and space, for it fails to state where the events take place or in what era. The absence of this information is important, for it gives the novel a very universal feel as the events could have taken place yesterday or 100 years ago to a married couple from any nation. This characteristic of the novel is just one of the many differences between Pinto's text and the film: while the first has the aforementioned characteristic. the movie cannot escape the period in which it was filrned. This is but one of the many differences between both texts to be explored in this paper from a comparative standpoint.